Application of reaching law approach to the position control of a vector controlled induction motor drive - Bayindir, MI; Can, H; Akpolat, ZH; Ozdemir, M; Akin, E (Springer, 2005)
In this paper, a new position control method based on the reaching law control (RLC) approach is proposed for the robust position control of electrical drive systems. The main aim of this study is to investigate the robustness of the RLC approach under inertial-frictional variations and external disturbances and to address the application problems of the RLC approach for position control systems. New components are added to the controller in order to improve the robustness. The control method is applied to a vector-controlled induction motor drive system. It is shown in the paper that the practical constraints such as torque limitation, and the demand of high control performance, i.e., high bandwidth, result in undesirable overshoots. The performance of the control method is shown by simulation and experimental results.
Keywords: sliding mode control; reaching law control; position control; induction motor